ICTV Virus Taxonomy Profile: Redondoviridae - Abbas, Arwa; Taylor, Louis J; Collman, Ronald G; Bushman, Frederic D; Ictv Report Consortium (Journal of general virology, 2021)
Viruses in the family have a circular genome of 3.0 kb with three open reading frames. The packaged genome is inferred to be single-stranded DNA by analogy to related viruses. Redondoviruses were discovered through metagenomic sequencing methods in samples from human subjects and are inferred to replicate in humans. Evidence of redondovirus infection is associated with periodontitis and critical illness, but redondoviruses have not been shown to be the causative agent of any diseases. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the family , which is available at ictv.global/report/redondoviridae.